1999
DOI: 10.1177/039139889902200909
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HCV Viremia following LDL Apheresis in a HCV Positive Patient with Familial Hypercholesterolemia

Abstract: It has been suggested that hepatitis C virus (HCV) can be associated with beta-lipoprotein in human serum. According to this, the LDL receptor could promote endocytosis of such a virus. In the present study, we evaluated the changes in HCV viremia in a HCV positive patient with familial hypercholesterolemia, undergoing both selective (DALI System, Fresenius) and non-selective (plasma exchange) LDL apheresis. HCV-RNA levels did not decrease following selective LDL apheresis, on the contrary showed a random, odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Marson et al . reported that low‐density lipoprotein‐cholesterol apheresis and plasma exchange in hypercholesteremia patients with HCV infection reduced the quantity of HCV‐RNA in the blood of some cases 11 . Ishida et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marson et al . reported that low‐density lipoprotein‐cholesterol apheresis and plasma exchange in hypercholesteremia patients with HCV infection reduced the quantity of HCV‐RNA in the blood of some cases 11 . Ishida et al .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Marson et al reported that low-density lipoprotein-cholesterol apheresis and plasma exchange in hypercholesteremia patients with HCV infection reduced the quantity of HCV-RNA in the blood of some cases. 11 Ishida et al found that hemodialysis, hemofiltration and peritoneal dialysis in chronic dialysis patients infected with HCV produced significantly lower HCV-RNA levels in the blood. 12 There are reports of combined granulocyte apheresis with IFN therapy for chronic hepatitis C, [13][14][15] and also reports claiming that early reduction of the virus is important in the treatment of chronic hepatitis C. 16,17 Thus, the potential effectiveness of IFN therapy combined with early virus removal by a physical method is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of the clinical results of plasmapheresis have been described, whereby HCV in the blood is related to the effects of IFN therapy that could be enhanced by removing the virus from blood [12][13][14] . Low-density lipoprotein-cholesterol apheresis and plasma exchange in hypercholesteremic patients with HCV infection reduces the quantity of HCV RNA in the blood of some patients [15] . Hemodialysis, hemofiltration and peritoneal dialysis in chronic dialysis patients infected with HCV significantly lower HCV RNA levels in the blood [16] .…”
Section: Discussionmentioning
confidence: 99%